Ethics in Action at the Refurbished Archaeological Museum of Ioannina, Epirus, Greece - Eleni Vasileiou (Journal of Conservation and Museum Studies, 2014)
The first exhibition of the Archaeological Museum of Ioannina (nothwestern Greece) was inaugurated in 1970, in a building designed by the Greek architect Aris Konstantinidis. The museum closed in 2003 in order to be refurbished. Five years later (2008), the new exhibition was completed following the latest museological trends with a focus on the education of a diverse public and with awareness of the museum’s role as keeper of the collective memory.  This article deals with the application of the ICOM Code of Ethics in the refurbished Archaeological Museum of Ioannina. More specifically, it examines the way in which the museum’s new exhibition applies display methods and undertakes educational activities in order to accomplish its role as an educational institution.